Aqueous dispersion and laminate

By using aqueous dispersions of polyolefins, unsaturated carboxylic acid polymers and amide-based waxes, the problem of high dynamic friction coefficient of heat sealant coating film is solved, and the coating film formation and maintenance with low dynamic friction coefficient is achieved, and the laminated body is improved Adhesive strength and heat sealing.

CN114761483BActive Publication Date: 2024-12-20MITSUI CHEMICALS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080084196.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-05
Filing Date
2020-12-03
Publication Date
2024-12-20
Estimated Expiration
2040-12-03

AI Technical Summary

Technical Problem

The existing heat sealant has a high dynamic friction coefficient for the coating film formed on the surface of the substrate, which affects the ease of transport and the efficiency of filling contents, and it is difficult to keep the dynamic friction coefficient low after the coating film is formed.

Method used

Using an aqueous dispersion containing polyolefins, unsaturated carboxylic acid polymers and amide-based waxes, a coating film with a low dynamic friction coefficient is formed by adjusting its component ratio and manufacturing method, and is used to prepare an adhesive layer on the surface of the substrate. Ensure that the coating film has little dynamic friction resistance after drying.

Benefits of technology

The coating film is immediately formed and maintained at a low dynamic friction coefficient after coating, the bonding strength and heat sealing of the laminated body are improved, and the bonding performance between the substrate and the adhered substance is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114761483B_ABST
    Figure CN114761483B_ABST
Patent Text Reader

Abstract

The present invention aims to provide an aqueous dispersion capable of forming a coating film having low dynamic friction resistance immediately after coating. The present invention comprises an aqueous dispersion containing a polyolefin (A), an unsaturated carboxylic acid polymer (B), an amide wax (C) and water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an aqueous dispersion and a laminate, and more particularly to an aqueous dispersion and a laminate obtained by using the aqueous dispersion. Background Art

[0002] In the past, in various industrial fields, it is known to bond substrates such as plastic films, vapor-deposited films, metal foils, paper, and nonwoven fabrics to each other or to other adherends by heat and pressure (i.e., heat sealing). When heat sealing, a method of directly bonding substrates to each other or to an adherend is generally used, but in order to improve the heat sealability of the substrate and the adherend, the following method is also used: a heat sealant (adhesive) layer is formed on the substrate in advance, and these substrates are bonded to each other or to other adherends via the adhesive layer.

[0003] As an adhesive that can be used for such heat sealing, for example, an aqueous dispersion containing a resin component and water has been proposed, wherein the resin component includes an ethylene-unsaturated carboxylic acid copolymer, a polymer having an acrylic ester unit as a polymerization unit, and an ethylene-vinyl acetate copolymer. In addition, a laminate in which the aqueous dispersion is applied to a substrate and dried to form a coating film on the surface of the substrate has also been proposed (for example, see Patent Document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2018 / 142997 Summary of the invention

[0007] Problems to be solved by the invention

[0008] From the viewpoint of improving the ease of carrying of the laminate in the workplace or the filling efficiency of the content, for the coating (heat sealant) formed on the substrate surface, it is required that the coefficient of kinetic friction on its surface is small. In addition, it is also desired that the coefficient of kinetic friction of the coating just after the coating is formed is small.

[0009] That is, an object of the present invention is to provide an aqueous dispersion capable of forming a coating film having low dynamic friction resistance immediately after coating, and to provide a laminate of a substrate and a coating film having low dynamic friction resistance.

[0010] Means for solving problems

[0011] The present invention relates to the following [1] to [7].

[0012] [1] An aqueous dispersion comprising a polyolefin (A), an unsaturated carboxylic acid polymer (B), an amide wax (C) and water.

[0013] [2] The aqueous dispersion according to [1] above, wherein the concentration of the amide wax (C) is 0.15 to 3.0 parts by mass based on 100 parts by mass of component (A) + component (B) of the aqueous dispersion.

[0014] [3] The aqueous dispersion according to [1] or [2], wherein the unsaturated carboxylic acid polymer (B) is at least one selected from the group consisting of an ethylene-unsaturated carboxylic acid copolymer (b1) and / or its salt (B1), and a (meth)acrylate polymer (B2).

[0015] [4] The aqueous dispersion as described in any one of [1] to [3] above, wherein the unsaturated carboxylic acid polymer (B) is a composite particle comprising the ethylene-unsaturated carboxylic acid copolymer (b1) and / or its salt (B1) and the (meth)acrylate polymer (B2).

[0016] [5] A laminate comprising a substrate and an adhesive layer laminated on at least a portion of at least one surface of the substrate, wherein the adhesive layer is formed from a dried product of the aqueous dispersion according to any one of [1] to [4] above.

[0017] [6] The laminate according to [5], further comprising an adherend layer laminated on a surface of the adhesive layer opposite to the substrate side.

[0018] [7] The laminate according to [5] or [6] above, wherein the substrate is made of aluminum.

[0019] Effects of the Invention

[0020] According to the aqueous dispersion of the present invention, a coating film having low dynamic friction resistance can be formed immediately after being applied to a substrate. In addition, the coating film of the laminate of the present invention has low dynamic friction resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] [ Figure 1 ] Figure 1 The relationship between the amount of wax added to the aqueous dispersion in Example 1 and Comparative Example 1 and the dynamic friction coefficient of the coating film formed from the aqueous dispersion is shown.

[0022] [ Figure 2 ] Figure 2 The relationship between the standing time after application of the aqueous dispersion and the dynamic friction coefficient of the coating film formed from the aqueous dispersion in Examples 1 and 2 and Comparative Example 2 is shown.

[0023] [ Figure 3 ] Figure 3 The relationship between the standing time after application of the aqueous dispersion and the retention rate of the dynamic friction coefficient of the coating film formed from the aqueous dispersion in Examples 1 and 2 and Comparative Example 2 is shown. DETAILED DESCRIPTION

[0024] Hereinafter, the present invention will be described in further detail.

[0025] [Aqueous dispersion]

[0026] The aqueous dispersion according to the present invention is characterized by containing a polyolefin (A), an unsaturated carboxylic acid polymer (B), an amide wax (C) and water.

[0027] <Polyolefin (A)>

[0028] The polyolefin (A) is a homopolymer of an olefin, a copolymer of two or more olefins, or a copolymer of an olefin and a diene.

[0029] Examples of the polyolefin (A) include:

[0030] Homopolymers or copolymers of α-olefins having 2 to 12 carbon atoms, such as ethylene, propylene, 1-butene, 3-methyl-1-butene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-heptene, 1-hexene, 1-decene, 1-dodecene, etc., represented by polyethylene such as low-density polyethylene and high-density polyethylene, polypropylene, poly-1-butene, poly-3-methyl-1-butene, poly-4-methyl-1-pentene, poly-3-methyl-1-pentene, ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-1-hexene copolymers such as linear low-density polyethylene (1-LDPE), and propylene-1-butene copolymers; and

[0031] Copolymers of α-olefins and conjugated dienes or non-conjugated dienes, such as ethylene-butadiene copolymers, ethylene-ethylidene norbornene copolymers, ethylene-propylene-butadiene terpolymers, ethylene-propylene-dicyclopentadiene terpolymers, and ethylene-propylene-1,5-hexadiene terpolymers.

[0032] From the viewpoint of improving the retention rate of the dynamic friction coefficient, the polyolefin polymer (A) includes a polymer having a density of 900 kg / m 3 Above, 940kg / m 3 The following ethylene homopolymer or ethylene-based copolymer of ethylene and α-olefin (A1) is a preferred embodiment.

[0033] The density of the ethylene polymer (A1) is preferably 900 kg / m 3 Above, 935kg / m 3 the following.

[0034] The melting point of the ethylene polymer (A1) measured by differential scanning calorimetry (DSC) under the following conditions is preferably 95° C. or higher and 140° C. or lower, more preferably 95° C. or higher and 130° C. or lower.

[0035] [DSC measurement conditions]

[0036] Using a differential scanning calorimeter, about 5.0 mg of a sample was heated from 30°C to 200°C at a heating rate of 10°C / min under a nitrogen atmosphere, and maintained at this temperature for 10 minutes. It was then cooled to 30°C at a cooling rate of 10°C / min, maintained at this temperature for 5 minutes, and then heated to 200°C at a heating rate of 10°C / min. The endothermic peak observed during the second heating was taken as the melting peak, and the temperature at which the melting peak appeared was taken as the melting point. When the melting peak is multimodal, the temperature at which the melting peak on the highest temperature side appears is taken as the melting point.

[0037] Examples of the α-olefin in the ethylene·α-olefin copolymer that can be used as the ethylene-based polymer (A1) include α-olefins having 3 to 12 carbon atoms, such as propylene, 1-butene, 3-methyl-1-butene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-heptene, 1-hexene, 1-decene, and 1-dodecene. Among these α-olefins, 1-hexene is preferred. The content (mol %) of the structural unit derived from the α-olefin in the ethylene·α-olefin copolymer is preferably 0.01 to 10 mol %.

[0038] The method for producing the ethylene polymer (A1) is not particularly limited as long as a polymer satisfying the above-mentioned desired properties can be obtained.

[0039] Specific examples of the ethylene-based polymer (A1) include low-density polyethylene and linear low-density polyethylene.

[0040] From the viewpoint of improving the low-temperature heat sealability of the laminate of the present invention, the polyolefin polymer (A) includes a polymer having a density of 860 kg / m 3 Above, 895kg / m 3 The following ethylene·α-olefin copolymer (A2) is a preferred embodiment.

[0041] The density of the ethylene·α-olefin copolymer (A2) is preferably 890 kg / m 3 Below, more preferably 880kg / m 3 In addition, the density of the ethylene·α-olefin copolymer (A2) is preferably 865 kg / m 3 above.

[0042] The melting point of the above-mentioned ethylene α-olefin copolymer (A2) measured by DSC is usually below 80°C, preferably below 70°C. It should be noted that, in the present invention, the so-called below 80°C refers to a polymer that does not have a melting point as described below. In addition, the above-mentioned melting point measured by DSC refers to the melting point measured by DSC under the conditions described in the part of the ethylene polymer (A1).

[0043] The ethylene / α-olefin copolymer (A2) may be amorphous, that is, may have no melting point, or may have a melting point of 40° C. or higher, or 50° C. or higher.

[0044] Examples of the α-olefin constituting the ethylene·α-olefin copolymer (A2) include α-olefins having 3 to 12 carbon atoms, such as propylene, 1-butene, 3-methyl-1-butene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-heptene, 1-hexene, 1-decene, and 1-dodecene. Among these α-olefins, 1-butene is preferred.

[0045] The content (mol %) of the structural unit derived from the α-olefin in the ethylene / α-olefin copolymer (A2) is preferably in the range of 5 to 50 mol %.

[0046] From the viewpoint of improving the retention rate of the dynamic friction coefficient and further improving the heat sealability, it is a preferred embodiment to include an ethylene polymer (A1) and an ethylene·α-olefin copolymer (A2) as the polyolefin (A). As a combination of the ethylene polymer (A1) and the ethylene·α-olefin copolymer (A2), for example, a low-density polyethylene and an ethylene·butene copolymer, a linear low-density polyethylene and an ethylene·butene copolymer,

[0047] From the viewpoint of achieving both an improvement in the retention rate of the dynamic friction coefficient and an improvement in the heat sealing properties, the mass ratio [(A1) / (A2)] of the ethylene polymer (A1) to the ethylene·α-olefin copolymer (A2) is preferably 90 / 10 to 10 / 90, more preferably 80 / 20 to 20 / 80.

[0048] These polyolefins may be used alone or in combination of two or more.

[0049] <Unsaturated carboxylic acid polymer (B)>

[0050] The unsaturated carboxylic acid polymer (B) is a polymer and / or a salt thereof containing an unsaturated carboxylic acid or a derivative (for example, an ester, anhydride, etc.) of an unsaturated carboxylic acid as a structural unit.

[0051] Examples of the unsaturated carboxylic acid polymer (B) include ethylene-unsaturated carboxylic acid copolymers (b1) and / or salts thereof (B1) which are copolymers of ethylene and unsaturated carboxylic acids, and (meth)acrylic acid ester polymers (B2) which are derivatives of unsaturated carboxylic acids.

[0052] <Ethylene-unsaturated carboxylic acid copolymer (b1) and / or its salt (B1)]

[0053] The ethylene-unsaturated carboxylic acid copolymer (b1) is a copolymer of ethylene and an unsaturated carboxylic acid.

[0054] The unsaturated carboxylic acid is a monomer having at least one ethylenically unsaturated bond and a carboxyl group in one molecule, and examples thereof include monobasic acids such as acrylic acid, methacrylic acid, and crotonic acid, and dibasic acids such as maleic acid, fumaric acid, and itaconic acid.

[0055] These unsaturated carboxylic acids may be used alone or in combination of two or more.

[0056] As the unsaturated carboxylic acid, from the viewpoint of water resistance, preferably, a monobasic acid is used, and more preferably, acrylic acid and methacrylic acid are used.

[0057] Regarding the content ratio of the structural unit derived from ethylene (hereinafter, also described as "ethylene unit") and the structural unit derived from unsaturated carboxylic acid (hereinafter, also described as "unsaturated carboxylic acid unit") in the above-mentioned ethylene·unsaturated carboxylic acid copolymer (b1), the ethylene unit is, for example, 75% by mass or more, preferably 78% by mass or more, for example, 90% by mass or less, preferably 88% by mass or less, relative to their total amount. In addition, the unsaturated carboxylic acid unit is, for example, 10% by mass or more, preferably 12% by mass or more, for example, 25% by mass or less, preferably 22% by mass or less.

[0058] When the content ratio of the ethylene unit and the unsaturated carboxylic acid unit in the ethylene-unsaturated carboxylic acid copolymer (b1) is within the above range, a coating film formed from the aqueous dispersion can exhibit excellent adhesive strength and anti-blocking properties.

[0059] There is no particular limitation on the polymerization method of ethylene and unsaturated carboxylic acid, and a known polymerization method can be adopted. Examples of the polymerization method include a method of contacting ethylene, unsaturated carboxylic acid and a known polymerization initiator such as peroxide under high temperature and high pressure conditions.

[0060] The above-mentioned ethylene·unsaturated carboxylic acid copolymer (b1) can be obtained in the form of a dispersion (aqueous dispersion) formed by dispersing its individual particles (hereinafter referred to as resin particles (I)) in water. In such a case, for example, polymerization can be carried out by the method described in Japanese Patent Publication No. 7-008933, Japanese Patent Publication No. 5-039975, Japanese Patent Publication No. 4-030970, Japanese Patent Publication No. 42-000275, Japanese Patent Publication No. 42-023085, Japanese Patent Publication No. 45-029909, Japanese Patent Publication No. 51-062890, etc. The ethylene·unsaturated carboxylic acid copolymer (b1) has self-emulsification.

[0061] In the production of the ethylene-unsaturated carboxylic acid copolymer (b1), an emulsifier (surfactant) described below may be added as necessary from the viewpoint of improving production stability. The mixing ratio of the emulsifier may be appropriately set.

[0062] In the production of the above-mentioned ethylene-unsaturated carboxylic acid copolymer (b1), from the viewpoint of achieving improved production stability, known additives such as pH adjusters, metal ion chelating agents such as ethylenediaminetetraacetic acid and its salts, molecular weight regulators (chain transfer agents) such as thiols and low molecular weight halides, etc. can be formulated in appropriate proportions.

[0063] As the ethylene-unsaturated carboxylic acid copolymer (b1) and / or its salt (B1), the salt (B1) of the ethylene-unsaturated carboxylic acid copolymer (b1) is preferred from the viewpoint of improving dispersion stability and printability of a laminate (described later).

[0064] The salt (B1) of the ethylene / unsaturated carboxylic acid copolymer (b1) can be prepared, for example, by adding a base to the ethylene / unsaturated carboxylic acid copolymer (b1), specifically, a dispersion of the ethylene / unsaturated carboxylic acid copolymer (b1).

[0065] Examples of the base include inorganic bases such as sodium hydroxide and potassium hydroxide, and organic bases such as amines such as ammonia, triethylamine, triethanolamine, and dimethylethanolamine.

[0066] These bases may be used alone or in combination of two or more.

[0067] As the base, preferably, an inorganic base is used, and more preferably, sodium hydroxide is used.

[0068] From the viewpoint of achieving improved dispersion stability and printability of a laminate (described later), the amount of base added (i.e., amount / valence) is, for example, 5 mol or more, preferably 30 mol or more, more preferably 50 mol or more, for example, 100 mol or less, preferably 95 mol or less, relative to 100 mol of carboxyl groups in the above-mentioned ethylene-unsaturated carboxylic acid copolymer (b1).

[0069] When the amount of the base added is above the lower limit, the dispersion stability of the aqueous dispersion is excellent and the printability of the laminate is excellent. In addition, when the amount of the base added is below the upper limit, the viscosity of the aqueous dispersion is not too high and the operability is excellent.

[0070] In addition, after adding the above-mentioned base to the above-mentioned ethylene-unsaturated carboxylic acid copolymer (b1), it is preferred to keep them at a predetermined temperature for a predetermined time. The holding temperature is, for example, 40° C. or more, preferably 50° C. or more, for example, 190° C. or less, preferably 180° C. or less. In addition, the holding time is, for example, 30 minutes or more, preferably 1 hour or more, for example, 12 hours or less, preferably 10 hours or less.

[0071] By maintaining the above conditions, the ethylene-unsaturated carboxylic acid copolymer (b1) is neutralized, and dispersion stability and printability of a laminate (described later) can be improved.

[0072] When the ethylene-unsaturated carboxylic acid copolymer (B1) is a salt of the ethylene-unsaturated carboxylic acid copolymer (b1), the degree of neutralization is, for example, 30% or more, preferably 50% or more, for example, 100% or less, preferably 95% or less.

[0073] When the degree of neutralization is within the above range, excellent adhesive strength and anti-blocking properties can be obtained. It should be noted that the degree of neutralization is calculated according to the method used in the examples described below.

[0074] The infrared absorption spectrum of the sample was measured to find the 1700 cm -1 The peak height of absorption (the peak height is set to a).

[0075] In addition, the sample was brought into contact with hydrochloric acid to remove the metal ions in the resin (demetallization) to obtain an acid copolymer without ionic bonding (intramolecular crosslinking). The infrared absorption spectrum of the sample of the acid copolymer was measured to obtain the infrared absorption spectrum at 1700 cm -1 The peak height of absorption (the peak height is set to b).

[0076] The peak height a corresponds to the number of carboxyl groups in the resin that are not ionically bonded.

[0077] In addition, the peak height b corresponds to the number of all carboxyl groups in the resin.

[0078] Therefore, the degree of neutralization (%) was calculated using the following formula.

[0079] Neutralization degree (%) = 100-100 × a / b

[0080] The weight average molecular weight of the ethylene-unsaturated carboxylic acid copolymer (b1) and / or its salt (B1) is measured by gel permeation chromatography (GPC) and converted to standard polystyrene, and is, for example, 5,000 or more, preferably 10,000 or more, for example, 1,000,000 or less, preferably 500,000 or less.

[0081] The melting point of the ethylene-unsaturated carboxylic acid copolymer (b1) and / or its salt (B1) measured by DSC (differential scanning calorimetry) is, for example, 55°C or higher, preferably 65°C or higher, for example, 110°C or lower, preferably 100°C or lower.

[0082] The solid content concentration of the ethylene·unsaturated carboxylic acid copolymer (b1) and / or its salt (B1) in the dispersion of the above-mentioned ethylene·unsaturated carboxylic acid copolymer (b1) and / or its salt (B1) is, for example, greater than 10 mass%, preferably greater than 20 mass%, for example, less than 60 mass%, preferably less than 50 mass%.

[0083] The dispersion of the ethylene-unsaturated carboxylic acid copolymer (b1) and / or its salt (B1) can also be obtained as a commercial product.

[0084] These ethylene-unsaturated carboxylic acid copolymers and / or their salts (B1) may be used alone or in combination of two or more.

[0085] From the viewpoint of improving the friction resistance retention of the obtained laminate, a mixture of ethylene-acrylic acid copolymer (b1-1) and / or its salt (B1-1) and ethylene-methacrylic acid copolymer (b1-2) and / or its salt (B1-2) as the dispersion of the above-mentioned ethylene-unsaturated carboxylic acid copolymer (b1) and / or its salt (B1) is also a preferred embodiment. The detailed mechanism of improving the friction resistance retention is unclear, but it is speculated that in the aqueous dispersion of the above-mentioned mixture, the polymer particles containing the polymer component are further refined and the film-forming performance is improved, which brings some help to the improvement of the above-mentioned physical properties.

[0086] <(Meth)acrylate polymer (B2)>

[0087] The (meth)acrylate polymer (B2) has at least a structural unit obtained from a (meth)acrylate (a (meth)acrylate monomer) (hereinafter, also referred to as a “(meth)acrylate unit”) as a structural unit.

[0088] In addition, the so-called (meth)acrylate is defined as acrylate and / or methacrylate.

[0089] Examples of the (meth)acrylate include (meth)acrylates having an alkyl portion having 1 to 12 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate.

[0090] These (meth)acrylates may be used alone or in combination of two or more.

[0091] Preferred examples of the (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; more preferred examples include methyl (meth)acrylate and n-butyl (meth)acrylate; and further preferred examples include methyl methacrylate, n-butyl methacrylate, and butyl acrylate.

[0092] Furthermore, the polymer (B2) may contain, as an optional component, a polymerized unit obtained from a copolymerizable monomer copolymerizable with a (meth)acrylic acid ester.

[0093] Examples of the copolymerizable monomer include functional group-containing vinyl monomers, aromatic vinyl monomers, N-substituted unsaturated carboxylic acid amides, heterocyclic vinyl compounds, vinylidene halide compounds, α-olefins, and dienes.

[0094] Examples of the functional group-containing vinyl monomer include carboxyl group-containing vinyl monomers, hydroxyl group-containing vinyl monomers, amino group-containing vinyl monomers, glycidyl group-containing vinyl monomers, cyano group-containing vinyl monomers, sulfonic acid group-containing vinyl monomers and salts thereof, acetoacetoxy group-containing vinyl monomers, phosphoric acid group-containing compounds, amide group-containing vinyl monomers, and vinyl esters.

[0095] Examples of the carboxyl group-containing vinyl monomer include (meth)acrylic acid, maleic anhydride, maleic acid, fumaric acid, itaconic acid, and crotonic acid.

[0096] Examples of the hydroxyl group-containing vinyl monomer include 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate.

[0097] Examples of the amino group-containing vinyl monomer include 2-aminoethyl (meth)acrylate, 2-(N-methylamino)ethyl (meth)acrylate, and 2-(N,N-dimethylamino)ethyl (meth)acrylate.

[0098] As a glycidyl group-containing vinyl monomer, glycidyl (meth)acrylate is mentioned, for example.

[0099] Examples of the cyano group-containing vinyl monomer include (meth)acrylonitrile.

[0100] Examples of the sulfonic acid group-containing vinyl monomer include allyl sulfonic acid and methallyl sulfonic acid. In addition, examples of salts thereof include alkali metal salts such as sodium salts and potassium salts of the above-mentioned sulfonic acid group-containing vinyl monomers, such as ammonium salts. Specifically, examples thereof include sodium allyl sulfonate, sodium methallyl sulfonate, and ammonium methallyl sulfonate.

[0101] As an acetoacetoxy group-containing vinyl monomer, acetoacetoxyethyl (meth)acrylate is mentioned, for example.

[0102] As a phosphoric acid group-containing compound, 2-methacryloyloxyethyl acid phosphate is mentioned, for example.

[0103] As an amide group-containing vinyl monomer, (meth)acrylamide is mentioned, for example.

[0104] Examples of the vinyl esters include vinyl propionate (excluding vinyl acetate).

[0105] Examples of the aromatic vinyl monomer include styrene, α-methylstyrene, and divinylbenzene.

[0106] As N-substituted unsaturated carboxylic acid amide, N-methylol (meth) acrylamide is mentioned, for example.

[0107] Examples of the heterocyclic vinyl compound include vinyl pyrrolidone.

[0108] Examples of the vinylidene halide compound include vinylidene chloride and vinylidene fluoride.

[0109] Examples of the α-olefins include ethylene and propylene.

[0110] As the dienes, for example, butadiene can be mentioned.

[0111] Furthermore, as the copolymerizable monomer, a crosslinkable vinyl monomer can also be mentioned.

[0112] Examples of the crosslinkable vinyl monomer include compounds containing two or more vinyl groups, such as methylenebis(meth)acrylamide, divinylbenzene, and polyethylene glycol chain-containing di(meth)acrylate.

[0113] These copolymerizable monomers may be used alone or in combination of two or more.

[0114] As the copolymerizable monomer, preferably, a vinyl monomer having a functional group is used.

[0115] Moreover, as a (meth)acrylate, methacrylate is preferable among acrylate and methacrylate from a viewpoint of water resistance.

[0116] Regarding the content ratio of the (meth)acrylate unit and the structural unit derived from other copolymerizable monomers (hereinafter, also described as "copolymerizable monomer unit") in the above-mentioned polymer (B2), when the total is set to 100 mass%, the (meth)acrylate unit is, for example, 50 mass% or more, preferably 70 mass% or more, and more preferably 77 mass% or more. In addition, the copolymerizable monomer unit is 50 mass% or less, preferably 30 mass% or less, and more preferably 23 mass% or less.

[0117] When the content ratio of the (meth)acrylic acid ester unit and the copolymerizable monomer unit is within the above range, excellent adhesive strength and anti-blocking property can be obtained.

[0118] That is, the polymer (B2) may not contain copolymerizable monomer units but may be formed only from (meth)acrylate units, or may be formed from (meth)acrylate components and copolymerizable monomer components in the above ratio. The polymer (B2) is preferably formed only from (meth)acrylate units, or from (meth)acrylate units and copolymerizable monomer units in the above ratio.

[0119] When the polymer (B2) is composed only of a (meth)acrylate unit, the (meth)acrylate is preferably composed only of a (meth)acrylate having an alkyl portion having 4 carbon atoms, or a combination of methyl (meth)acrylate and a (meth)acrylate having an alkyl portion having 4 carbon atoms.

[0120] When the (meth)acrylate is composed only of a (meth)acrylate having an alkyl portion having 4 carbon atoms, the (meth)acrylate is particularly preferably composed only of n-butyl methacrylate or a combination of n-butyl methacrylate and n-butyl acrylate.

[0121] In addition, when the (meth)acrylate is a combination of methyl (meth)acrylate and a (meth)acrylate having an alkyl portion having 4 carbon atoms, the (meth)acrylate is particularly preferably a combination of methyl methacrylate and n-butyl methacrylate, or a combination of methyl methacrylate and n-butyl acrylate.

[0122] When the (meth)acrylate is such a combination, the glass transition temperature of the polymer (B2) can be adjusted to the range described below.

[0123] When the other copolymerizable monomer is a carboxyl group-containing vinyl monomer, the proportion of the structural unit derived from the carboxyl group-containing vinyl monomer in the polymer (B2) is, for example, 5 mass % or less, preferably 3 mass % or less, from the viewpoint of production stability.

[0124] The method for producing the polymer (B2) is not particularly limited, and a known method can be used. An example of the production method is a method in which water, a (meth)acrylate component, and a polymerization initiator are mixed and the (meth)acrylate component is polymerized in water.

[0125] The polymerization initiator is not particularly limited, and examples thereof include:

[0126] Hydrogen peroxide;

[0127] Persulfates such as ammonium persulfate, potassium persulfate, sodium persulfate, etc.

[0128] Organic peroxides such as cumene hydroperoxide, tert-butyl hydroperoxide, benzoyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl perbenzoate, and lauroyl peroxide; and

[0129] Azo compounds such as azobisisobutyronitrile; and

[0130] The redox initiator is formed by combining these with metal ions such as iron ions and reducing agents such as sodium sulfoxylate, formaldehyde, sodium pyrosulfite, sodium bisulfite, L-ascorbic acid, and Rongalite. These polymerization initiators may be used alone or in combination of two or more.

[0131] The mixing ratio of the polymerization initiator can be appropriately set, and is, for example, 0.1% by mass or more, and, for example, 5% by mass or less, based on the total amount of the monomer components.

[0132] In the polymerization, a molecular weight modifier may be added as necessary.

[0133] As the molecular weight modifier, for example, thiols such as tert-dodecyl mercaptan and n-dodecyl mercaptan, allyl compounds such as allyl sulfonic acid, methallyl sulfonic acid and their sodium salts can be cited. These molecular weight modifiers can be used alone or in combination of two or more. The proportion of the molecular weight modifier can be appropriately set.

[0134] When the polymerization is carried out under normal pressure, the polymerization temperature is, for example, 30° C. or more, preferably 50° C. or more, for example, 95° C. or less, preferably 85° C. or less. The polymerization time is, for example, 1 hour or more, preferably 2 hours or more, for example, 30 hours or less, preferably 20 hours or less.

[0135] In the production of the polymer (B2), an emulsifier (surfactant) may be added as necessary from the viewpoint of improving production stability.

[0136] Examples of the emulsifier (surfactant) include anionic surfactants, nonionic surfactants, and cationic surfactants.

[0137] Examples of the anionic surfactant include sodium dodecylbenzenesulfonate, sodium lauryl sulfate, sodium alkyl diphenyl ether disulfonate, sodium alkyl naphthalene sulfonate, sodium dialkyl sulfosuccinate, sodium stearate, potassium oleate, dioctyl sodium sulfosuccinate, sodium polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene alkylphenyl ether sulfate, sodium dialkyl sulfosuccinate, sodium oleate, and sodium salt of tert-octylphenoxyethoxypolyethoxyethyl sulfate.

[0138] Examples of the nonionic surfactant include polyoxyethylene lauryl ether, polyoxyethylene octylphenyl ether, polyoxyethylene oleylphenyl ether, polyoxyethylene nonylphenyl ether, oxyethylene-oxypropylene block copolymers, tert-octylphenoxyethylpolyethoxyethanol, and nonylphenoxyethylpolyethoxyethanol.

[0139] Examples of the cationic surfactant include lauryltrimethylammonium chloride and stearyltrimethylammonium chloride.

[0140] These emulsifiers (surfactants) may be used alone or in combination of two or more.

[0141] As the emulsifier (surfactant), preferably an anionic surfactant is used, and more preferably sodium dodecylbenzenesulfonate is used.

[0142] The mixing ratio of the emulsifier (surfactant) is not particularly limited, but is, from the viewpoint of production stability, for example, 0.02 parts by mass or more and 5 parts by mass or less based on 100 parts by mass of the total amount of the (meth)acrylate and any other copolymer monomers.

[0143] In the production of the above-mentioned polymer (B2), from the viewpoint of achieving improved production stability, known additives such as pH adjusters, metal ion chelating agents such as ethylenediaminetetraacetic acid and its salts, molecular weight regulators (chain transfer agents) such as thiols and low molecular weight halides, etc. can be added in appropriate proportions.

[0144] The weight average molecular weight of the polymer (B2) is, for example, 5,000 or more, preferably 10,000 or more, and for example, 1,000,000 or less, preferably 500,000 or less, as measured by gel permeation chromatography (GPC) and converted to standard polystyrene.

[0145] The glass transition temperature of the polymer (B2) is, for example, -28°C or higher, preferably -10°C or higher, for example, 80°C or lower, preferably 60°C or lower. When the glass transition temperature of the polymer (B2) is within the above range, excellent adhesive strength and anti-blocking properties can be obtained.

[0146] In particular, from the viewpoint of improving the adhesive strength of the aqueous dispersion, the glass transition temperature of the polymer (B2) is preferably 20° C. or lower, more preferably 10° C. or lower.

[0147] Furthermore, from the viewpoint of improving the anti-blocking property of the aqueous dispersion, the glass transition temperature of the polymer (B2) is preferably higher than 0°C, more preferably 10°C or higher.

[0148] <Amide wax (C)>

[0149] The amide wax (C) is a compound having a long-chain fatty acid group and an amide group in the molecule.

[0150] Examples of the amide wax (C) include amide compounds obtained by reacting a monocarboxylic acid with a monoamine or a monocarboxylic acid with a diamine, amide compounds obtained by reacting a monoamine with a polybasic acid, and amide compounds obtained by reacting a monocarboxylic acid, a polybasic acid, and a diamine.

[0151] As the monoamine, preferably a monoamine having 5 or more carbon atoms, exemplified by amylamine, hexylamine, heptylamine, octylamine, nonylamine, decylamine, dodecylamine, stearylamine, cyclohexylamine, benzylamine, etc. These may be used alone or in combination of two or more. Among them, aliphatic monoamines having 10 to 20 carbon atoms are particularly preferred.

[0152] The monocarboxylic acid is preferably an aliphatic monocarboxylic acid and hydroxycarboxylic acid having 5 or more carbon atoms, and examples thereof include valeric acid, caproic acid, caprylic acid, lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, behenic acid, montanic acid, 12-hydroxystearic acid, benzoic acid, etc. These can be used alone or in combination of two or more. Among them, aliphatic monocarboxylic acids having 10 to 30 carbon atoms are particularly preferred.

[0153] Specific examples of the above diamines include ethylenediamine, 1,3-diaminopropane, 1,4-diaminopropane, tetramethylenediamine, hexamethylenediamine, nonamethylenediamine, undecamethylenediamine, dodecamethylenediamine, meta-xylylenediamine, para-xylylenediamine, toluenediamine, phenylenediamine, and isophoronediamine. These may be used alone or in combination of two or more. Among them, ethylenediamine is particularly preferred.

[0154] The polybasic acid refers to a carboxylic acid of a dibasic acid or higher, and specific examples thereof include aliphatic dicarboxylic acids such as malonic acid, succinic acid, adipic acid, sebacic acid, pimelic acid, and azelaic acid, aromatic dicarboxylic acids such as phthalic acid, terephthalic acid, and isophthalic acid, and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid and cyclohexylsuccinic acid. These may be used alone or in combination of two or more.

[0155] Specific examples of the amide wax (C) include N-oleyl palmitamide, ethylene bisoleamide, and N-stearyl erucamide.

[0156] <Other ingredients>

[0157] The aqueous dispersion of the present invention may contain polymers (such as ethylene-vinyl acetate copolymer) or additives other than the above-mentioned components (A), (B) and (C).

[0158] As additives, for example, the above-mentioned emulsifiers, and curing agents, crosslinking agents, film-forming aids, defoamers, anti-cratering agents, leveling agents, tackifiers, hardness imparting agents, preservatives, thickeners, antifreeze agents, dispersants, inorganic pigments, organic pigments and other known additives can be enumerated. These additives can be used alone or in combination of two or more. The mixing ratio of the additives and the timing of mixing can be appropriately set according to the purpose and use.

[0159] <Aqueous dispersion>

[0160] The aqueous dispersion of the present invention is a dispersion containing the polyolefin (A), the unsaturated carboxylic acid polymer (B), the amide wax (C) and water. The content ratio of these components can be appropriately set according to the purpose and application.

[0161] When the total amount of the polyolefin (A) and the unsaturated carboxylic acid polymer (B) is 100% by mass, the content of the polyolefin (A) in the aqueous dispersion of the present invention is, for example, 30% by mass or more, preferably 45% by mass or more, more preferably 50% by mass or more, further preferably 60% by mass or more, for example, 70% by mass or less, preferably 65% ​​by mass or less, more preferably 60% by mass or less.

[0162] When the total amount of the polyolefin (A) and the unsaturated carboxylic acid polymer (B) is 100% by mass, the content of the unsaturated carboxylic acid polymer (B) in the aqueous dispersion of the present invention is, for example, 30% by mass or more, preferably 35% by mass or more, more preferably 40% by mass or more, for example, 70% by mass or less, preferably 55% by mass or less, more preferably 50% by mass or less, and further preferably 40% by mass or less.

[0163] When the content ratio of the polyolefin (A) to the unsaturated carboxylic acid polymer (B) is within the above range, excellent adhesive strength can be obtained, and the effect of adding the amide wax is likely to be rapidly exhibited.

[0164] The amount of the amide wax (C) contained in the aqueous dispersion of the present invention is 0.15 to 3.0 parts by mass, preferably 0.15 to 2.5 parts by mass, and more preferably 0.2 to 2.0 parts by mass, relative to 100 parts by mass of the components (A) and (B) of the aqueous dispersion.

[0165] In addition, the solid content of the aqueous dispersion refers to the components other than water and the organic solvent (which may be contained as an optional component) among the components contained in the aqueous dispersion of the present invention.

[0166] <Method for producing aqueous dispersion>

[0167] Examples of the method for producing the aqueous dispersion of the present invention include a method of mixing the above components at the above-mentioned predetermined ratio and emulsifying at once, and a method of emulsifying the individual components and then mixing them at the above-mentioned predetermined ratio.

[0168] In the aqueous dispersion of the present invention, the polymer component (i.e., polyolefin (A) and component (B)) may be contained in the form of a non-particulate polymer or in the form of a particulate polymer. Preferably, the polymer component is contained in the form of a particulate polymer.

[0169] The weight average particle size of the particles (measurement method: light scattering measurement) is, for example, 10 nm or more, for example, 10 μm or less, and preferably 5 μm or less.

[0170] When the polymer component is contained in the aqueous dispersion in the form of a particulate polymer, the polymer component may be single particles of each polymer or may be composite particles composed of two or more polymers.

[0171] For example, the ethylene-unsaturated carboxylic acid copolymer (b1) and / or its salt (B1) and the (meth)acrylic acid ester polymer (B2) can form composite particles.

[0172] The method for producing such composite particles is not particularly limited, and a known method can be adopted.

[0173] The morphology of the composite particles is not particularly limited, and examples thereof include a core / shell structure, a composite structure, a localized structure, a tumbler-shaped structure, an octopus-shaped structure, a raspberry-shaped structure, a multi-particle composite structure, and an IPN structure.

[0174] The solid content concentration of the aqueous dispersion of the present invention is, for example, 10 mass % or more, preferably 20 mass % or more, and for example, 60 mass % or less, preferably 50 mass % or less.

[0175] The pH of the aqueous dispersion of the present invention is, for example, 7 or more, for example, 11 or less, and preferably 10 or less.

[0176] The aqueous dispersion of the present invention can exhibit low friction properties quickly after being applied to a substrate.

[0177] When the aqueous dispersion of the present invention is used to form an adhesive layer (heat seal layer) of a laminate, a laminate having excellent adhesive strength can be obtained.

[0178] Therefore, the aqueous dispersion can be suitably used as an adhesive composition for forming an adhesive layer in a laminate including a substrate and an adhesive layer laminated on at least one surface of the substrate.

[0179] <Laminated body>

[0180] The laminate of the present invention comprises: a substrate; and an adhesive layer laminated on at least a part of at least one surface of the substrate.

[0181] Examples of the substrate include a resin substrate, a metal substrate, and a composite substrate.

[0182] Examples of the resin substrate include plastic films, containers, and cups formed from plastic materials such as cellophane, polyethylene, ethylene-vinyl acetate copolymers, ionomers, polypropylene, polyamide (nylon), polyester, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl alcohol copolymers, polycarbonate, polystyrene, and polyacrylonitrile copolymers.

[0183] Examples of the metal substrate include a metal plate, a metal foil, a container, and a cup. Examples of the metal include aluminum, gold, silver, copper, nickel, zinc, titanium, cobalt, indium, and chromium.

[0184] Examples of the composite substrate include a vapor-deposited film obtained by vapor-depositing a metal (aluminum, gold, silver, copper, nickel, zinc, titanium, cobalt, indium, chromium, etc.) or an oxide thereof (aluminum oxide, silicon oxide, etc.) on the above-mentioned plastic film.

[0185] Moreover, as a base material, paper and nonwoven fabric are mentioned, for example.

[0186] These substrates may be used alone or in combination of two or more.

[0187] As the substrate, preferably, a metal substrate is used, more preferably, a metal substrate composed of aluminum is used, and further preferably, a metal foil composed of aluminum is used.

[0188] The substrate may be subjected to surface treatment as required. Examples of surface treatment include ink (solvent-based, water-based) coating, electroplating, coupling, vacuum plasma treatment, etc. Preferably, ink coating, more preferably, solvent-based ink coating.

[0189] The adhesive layer is a dried product of the above-mentioned aqueous dispersion, and can be obtained by applying (coating) the above-mentioned aqueous dispersion on one surface of a substrate and drying it.

[0190] The aqueous dispersion may be applied to the entire surface of one side of the substrate, or, if the aqueous dispersion is used to form a heat seal layer, may be applied to a portion of one side of the substrate where the laminate is heat-sealed (bonded) to another material.

[0191] The method for applying (coating) the aqueous dispersion is not particularly limited, and for example, a known method such as gravure coating, three-roll coating, dip coating, spray coating, etc. can be used.

[0192] When the applied aqueous dispersion coating is dried, the drying temperature is, for example, 100 to 200° C., and the drying time is, for example, 10 seconds to 30 minutes.

[0193] Furthermore, before coating and drying, in order to improve the adhesion between the substrate and the adhesive layer, a primer (titanate, polyethyleneimine, etc.) may be applied to the substrate, or pretreatment such as corona discharge treatment or chemical conversion treatment may be performed.

[0194] According to such a laminate, the above-mentioned aqueous dispersion is used for the heat seal layer (adhesive layer), so that excellent bonding strength and low friction can be obtained. In addition, the aqueous dispersion of the present invention is not a dispersion in which particles are dispersed in an organic solvent such as ethyl acetate and toluene, so the residual organic solvent content in the adhesive layer can be preferably 100 ppm or less, more preferably 10 ppm or less.

[0195] Therefore, the laminate of the present invention can be used as a heat-sealing material in various industrial fields.

[0196] During heat sealing, the substrate and the adherend layer are bonded together via the adhesive layer.

[0197] The adherend layer is a material to be bonded to the above-mentioned laminate, and examples thereof include resin materials, metal materials, and composite materials.

[0198] Examples of the resin material include plastic films formed from plastic materials such as cellophane, polyethylene, ethylene-vinyl acetate copolymer, ionomer, polypropylene, polyamide (nylon), polyester, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, polycarbonate, polystyrene, and polyacrylonitrile copolymer.

[0199] Examples of the metal material include metal plates and metal foils, and examples of the metal include aluminum, gold, silver, copper, nickel, zinc, titanium, cobalt, indium, and chromium.

[0200] Examples of the composite material include a vapor-deposited film obtained by vapor-depositing a metal (aluminum, gold, silver, copper, nickel, zinc, titanium, cobalt, indium, chromium, etc.) or an oxide thereof (aluminum oxide, silicon oxide, etc.) on the above-mentioned plastic film.

[0201] Moreover, as an adherend layer, paper and nonwoven fabric are mentioned, for example.

[0202] In addition, the adherend layer may be subjected to surface treatment as required. As surface treatment, for example, ink (solvent system, water system) coating treatment, electroplating treatment, coupling treatment, vacuum plasma treatment can be cited, preferably ink coating treatment can be cited, and more preferably solvent-based ink coating treatment can be cited.

[0203] Moreover, as an adherend layer, a laminated body including a base material and an adhesive layer can also be mentioned.

[0204] These adherend layers may be used alone or in combination of two or more.

[0205] As the adherend layer, from the viewpoint of adhesive strength and ease of adhesion, preferably, a plastic film made of polyvinyl chloride or polyvinylidene chloride is used.

[0206] As the method of heat sealing the substrate and the adherend layer, there is no particular restriction, and a known method can be adopted. For example, a method of laminating the substrate and the adherend layer via an adhesive layer, and then heating and pressurizing can be cited. It should be noted that, when using the laminate of the present invention as the adherend layer, the adhesive layers are laminated to each other, and two substrates are laminated via these two layers of adhesive layers, and heated and pressurized.

[0207] The heating temperature is, for example, 80° C. or higher, preferably 100° C. or higher, for example, 250° C. or lower, preferably 200° C. or lower. The pressure is, for example, 50 kPa or higher, preferably 100 kPa or higher, for example, 500 kPa or lower, preferably 300 kPa or lower.

[0208] Thereby, the substrate and the adherend layer are heat-sealed (thermocompression-bonded).

[0209] The adhesive strength between the substrate and the adherend layer can be measured by the peel strength between the substrate and the adherend layer.

[0210] In addition, the laminated body in which the adherend layer is laminated on one surface of the adhesive layer in the above manner is included in the present invention regardless of the heat-sealed state (ie, before and after heat sealing).

[0211] Furthermore, since such a laminate is obtained using the above-mentioned aqueous dispersion, it is excellent in low friction.

[0212] Furthermore, such a laminate has excellent adhesive strength.

[0213] Therefore, the laminate can be suitably used as a packaging material in various industrial fields.

[0214] The packaged article to be packaged by the laminate is not particularly limited, and examples thereof include various industrial products such as snacks, foods, daily necessities, pharmaceuticals, and paper products.

[0215] In particular, in the field of pharmaceutical and food packaging, it is expected that the effects of suppressing the deterioration of packaging materials and packaged objects during heat sealing, increasing the productivity and reducing power consumption due to the high filling speed, etc. In addition, since the adhesive composition used to form the adhesive layer is an aqueous dispersion, it has the advantage of having a small load on the environment.

[0216] Example

[0217] Hereinafter, the present invention will be described in detail with reference to Examples and Comparative Examples, but the present invention is not limited thereto.

[0218] [Evaluation method]

[0219] The aqueous dispersions and laminates produced in Examples and the like were evaluated by the following methods.

[0220] <Particle size>

[0221] The particle size of the solid content in the aqueous dispersion produced in Examples etc. was measured by using a laser diffraction / scattering particle size distribution measuring apparatus Microtrac series to measure the particle size of each dispersion.

[0222] <Dynamic friction resistance>

[0223] The dynamic friction coefficient (COF) of the coating film of the laminated body produced in Examples etc. was measured by moving the coating film surfaces at a speed of 100 mm / min using a friction measuring machine TR-2 (manufactured by Toyo Seiki Seisaku-sho, Ltd.).

[0224] In addition, the dynamic friction coefficient retention rate was calculated using the following formula.

[0225] Dynamic friction coefficient retention rate (%) = (dynamic friction coefficient of the dry coating film after a predetermined time has passed since the laminate was produced / dynamic friction coefficient of the dry coating film immediately after the laminate was produced)

[0226] ×100

[0227] <Heat sealability>

[0228] The laminated body prepared in the examples was left at room temperature for one day and night, then cut into strips with a width of 15 mm. The dried coating films were stacked on top of each other and heated at a temperature of 110° C. and a pressure of 2 kgf / cm 2 The test piece was heat-sealed for 0.5 seconds under the condition of , and the 180-degree peel strength was measured under the condition of a pulling speed of 200 mm / second using the obtained test piece.

[0229] [Example 1]

[0230] <Manufacturing of aqueous dispersion>

[0231] Using Japanese Patent Application Laid-Open No. 63-46273 Figure 1In the kneading device described in the invention, a high-pressure low-density polyethylene (a polyolefin (A) [manufactured by DOW-MITSUI POLYCHEMICALS, trade name: MIRASON FL60, hereinafter also referred to as "LDPE"].] and an ethylene-acrylic acid copolymer (manufactured by DOW-MITSUI POLYCHEMICALS, trade name: NUCREL (ethylene content: 72% by mass), hereinafter also referred to as "EAA") as an unsaturated carboxylic acid polymer (B) were added into the hopper of the kneading device at a weight ratio of 5 / 5, and melt kneading was performed. During the melt kneading, an aqueous potassium hydroxide solution was added into the kneading device so that the degree of neutralization of the acrylic acid unit in the ethylene-acrylic acid copolymer became 50%, thereby neutralizing the acrylic acid component. Then, water and an amide wax, namely N-oleyl palmitamide, in an amount of 0.3 parts by mass relative to 100 parts by mass of the total amount of the resin component were supplied to the kneading device, and the mixture in the kneading device was cooled to room temperature. Finally, water was further added to obtain an aqueous dispersion with a solid content concentration of 40% by mass.

[0232] The particle size of the solid content in the obtained water dispersion was 2 μm.

[0233] <Manufacturing of laminated body>

[0234] Deionized water was added to the obtained aqueous dispersion to adjust the solid content concentration to 24%, and then the dispersion was coated with a Meyer bar at a coating amount of 3 g / m 2 The aqueous dispersion was applied to the entire surface of one surface of an aluminum foil (thickness: 40 μm) in a molten-liquid manner and dried at 120° C. for 30 seconds to obtain a laminate consisting of a soft aluminum foil and a dry coating film of the aqueous dispersion.

[0235] [Examples 2 to 5]

[0236] The same operation as in Example 1 was performed except that the amount of the amide wax used in preparing the water dispersion was changed to 0.5 parts by mass, 1.0 parts by mass, 1.5 parts by mass, and 2.0 parts by mass, respectively, relative to 100 parts by mass of the total amount of the resin component, to obtain three water dispersions of Examples 2 to 5 (all with a particle size of 2 μm). Next, using these water dispersions, the same operation as in Example 1 was performed to obtain laminates of Examples 2 to 5, respectively.

[0237] The results of measuring the dynamic friction coefficients of the laminates of Examples 1 to 5 are shown in Figures 1 to 3 The evaluation results of the heat sealing properties of Example 1 are shown in Table 1.

[0238] [Comparative Example 1]

[0239] The same operation as in Example 1 was carried out except that no wax was added to obtain an aqueous dispersion of Comparative Example 1. The same method as in the production method of the laminate of Example 1 was carried out using the aqueous dispersion to produce a laminate of Comparative Example 1.

[0240] The results of measuring the dynamic friction coefficient of the laminate are shown in Figure 1 .

[0241] [Example 6]

[0242] The same operation as in Example 1 was performed except that the wax was changed to ethylenebisoleamide which is an amide wax and the concentration of the wax was adjusted to only 0.3 parts by mass relative to 100 parts by mass of the total amount of the resin component to obtain an aqueous dispersion of Example 6. Next, using this aqueous dispersion, the same operation as in Example 1 was performed to obtain a laminate of Example 6. The particle size of the solid content in the aqueous dispersion was 2 μm.

[0243] The results of measuring the dynamic friction coefficient of the laminate are shown in Figure 2 and Figure 3 .

[0244] [Comparative Examples 2 to 5]

[0245] The same operation as in Example 1 was performed except that the wax was changed to polyethylene wax (manufactured by Mitsui Chemicals, Inc., trade name: W200) and the concentration of the wax was adjusted to 0.5 parts by mass, 1.0 parts by mass, 1.5 parts by mass, and 2.0 parts by mass relative to the total amount of the resin component to obtain aqueous dispersions of Comparative Examples 2 to 5. Next, using these aqueous dispersions, the same operation as in Example 1 was performed to obtain laminates of Comparative Examples 2 to 5.

[0246] The particle size of the solid content in the aqueous dispersions of Comparative Examples 2 to 5 was 2 μm in all cases. The results of measuring the dynamic friction coefficient of the laminate are shown in FIG. Figure 1 .

[0247] [Comparative Example 6]

[0248] Ethylene-methacrylic acid copolymer [manufactured by DOW-MITSUI POLYCHEMICALS (KK), trade name: NUCREL (ethylene content 85 mass%), hereinafter also referred to as "EMAA"]. ], potassium hydroxide, water, and N-oleyl palmitamide (0.3 mass% of the total resin component) were placed in an autoclave and stirred for 4 to 8 hours at a temperature of 130°C to 180°C and under pressure. Then, the mixture was cooled to room temperature to obtain an aqueous dispersion of Comparative Example 6 having a solid content concentration of 42 mass% and a good dispersion state. Next, the laminate of Comparative Example 6 was obtained using the aqueous dispersion. The particle size of the solid content in the aqueous dispersion was 2.0 μm.

[0249] The results of measuring the dynamic friction coefficient of the laminate are shown in Figure 2 and Figure 3 The evaluation results of heat sealability are shown in Table 1.

[0250] [Table 1]

[0251]

[0252] When the heat seal strength was 2.5 N / 15 mm or more, it was judged as OK.

[0253] [Examples 7 to 16, Comparative Examples 7 and 8]

[0254] The composition of the aqueous dispersion was changed to the composition shown in Table 2 below, and the aqueous dispersions of Examples 7 to 16 and Comparative Examples 7 and 8 were prepared in the same manner as in Example 1. Then, using these, laminates of Examples 7 to 16 and Comparative Examples 7 and 8 were obtained, respectively. In Table 2, Evolue SP0540 manufactured by Prime Polymer was used as l-LDPE, TAFMERDF7350 manufactured by Mitsui Chemicals was used as ethylene-butene copolymer, NUCREL manufactured by DOW-MITSUI POLYCHEMICALS (ethylene content: 72% by mass) was used as ethylene-acrylic acid copolymer, NUCREL manufactured by DOW-MITSUI POLYCHEMICALS (ethylene content: 91% by mass) was used as ethylene-methacrylic acid copolymer 1, and NUCREL manufactured by DOW-MITSUI POLYCHEMICALS (ethylene content: 85% by mass) was used as ethylene-methacrylic acid copolymer 2.

[0255] [Table 2]

[0256]

[0257] The same operation as in Example 1 was performed to obtain the dynamic friction coefficient (initial COF) immediately after the laminate was manufactured, the dynamic friction coefficient 3 hours after the laminate was manufactured (COF after 3 hours), the dynamic friction coefficient retention rate 3 hours after the laminate was manufactured (COF retention rate after 3 hours), and the heat seal strength of each laminate obtained. The results are shown in Table 2. It should be noted that, as a comprehensive judgment, an initial COF of less than 0.28 and a COF retention rate of more than 50% after 3 hours were set as OK, and other cases were set as NG.

[0258] <Discussion>

[0259] Figure 1 The figure shows the effect of the amount of polyethylene wax and amide wax added and the coefficient of dynamic friction (immediately after coating). Figure 1It is found that the water dispersion of Example 1 using amide wax as the wax has a smaller dynamic friction coefficient than the water dispersion of Comparative Example 6 using polyethylene wax as the wax.

[0260] Figure 2 The relationship between the standing time after the water dispersion coating and the dynamic friction coefficient is shown. Figure 2 It can be seen that the aqueous dispersions of Examples 1 and 6 (resin component: LDPE / EAA=5 / 5 (wax amount: 0.3 mass part)) show a lower dynamic friction coefficient in a short time after coating compared with the aqueous dispersion of Comparative Example 6 (resin component: EMAA=100% (wax amount: 0.3 mass part)).

[0261] Figure 3 The relationship between the standing time after the water dispersion coating and the retention rate of the dynamic friction coefficient is shown. Figure 3 It can be seen that the dynamic friction coefficient retention rate of the dried coating films formed from the water dispersions of Examples 1 and 6 after 3 hours from coating (i.e., from the production of the laminate) is about 80%. In contrast, the same retention rate of the dried coating film formed from the water dispersion of Comparative Example 6 is 40%, which shows that the dynamic friction coefficient changes greatly due to the standing time after coating.

[0262] From the results of the heat seal strength of Examples 8 to 16 in Table 2, it is understood that in the present invention, the heat seal strength at low temperatures can be improved by using two types of polyolefins (A) in combination.

Claims

1. A water dispersion comprising a polyolefin (A), an unsaturated carboxylic acid polymer (B), an amide wax (C) and water, in, The polyolefin (A) contains at least one selected from the group consisting of low-density polyethylene and linear low-density polyethylene, When the total amount of the polyolefin (A) and the unsaturated carboxylic acid polymer (B) is 100% by mass, the content of the unsaturated carboxylic acid polymer (B) in the aqueous dispersion is 30% by mass or more and 70% by mass or less, The concentration of the amide wax (C) is 0.15 to 3.0 parts by mass based on 100 parts by mass of the component (A) + the component (B) of the aqueous dispersion.

2. The aqueous dispersion according to claim 1, wherein The unsaturated carboxylic acid polymer (B) is at least one selected from the group consisting of an ethylene-unsaturated carboxylic acid copolymer (b1) and / or a salt thereof (B1), and a (meth)acrylic acid ester polymer (B2).

3. The aqueous dispersion according to claim 2, wherein The unsaturated carboxylic acid polymer (B) is a composite particle comprising the ethylene·unsaturated carboxylic acid copolymer (b1) and its salt (B1) and the (meth)acrylate polymer (B2), or the unsaturated carboxylic acid polymer (B) is a composite particle comprising the ethylene·unsaturated carboxylic acid copolymer (b1) and the (meth)acrylate polymer (B2), or the unsaturated carboxylic acid polymer (B) is a composite particle comprising the salt (B1) of the ethylene·unsaturated carboxylic acid copolymer (b1) and the (meth)acrylate polymer (B2). 4 . A laminate comprising a substrate and an adhesive layer laminated on at least a part of at least one surface of the substrate, wherein the adhesive layer is formed from a dried product of the aqueous dispersion according to claim 1 . 5 . The laminate according to claim 4 , further comprising an adherend layer laminated on a surface of the adhesive layer opposite to the substrate side.

6. The laminate according to claim 4 or 5, wherein: The substrate is formed of aluminum.